Health consumer engagement in developing novel preventive health community pharmacy roles in cardiovascular disease in Saudi Arabia: A qualitative analysis - Hadi A. Almansour; Nouf M. Aloudah; Tariq M. Alhawassi; Betty Chaar; Ines Krass; Bandana Saini (Elsevier, 2020)
Introduction: Cardiovascular diseases (CVD) are one of key leading causes of mortality worldwide. Both modifiable and non-modifiable risk factors contribute to the development of CVD. Modifiable risk factors such as smoking, unhealthy diets and lack of exercise are increasing in prevalence in Saudi Arabia but may be mitigated using pharmacological and non-pharmacological approaches. Thus, identifying, assessing and managing these modifiable risks at an early stage is essential. Pharmacists are highly accessible primary health professionals and can play a crucial role in screening and managing these risk factors in collaboration with primary care physicians. There is currently no research in Saudi Arabia exploring the views of health consumers with CVD risk factors regarding their preferences for or willingness to engage with community pharmacy CVD preventive health services. Objectives: To explore the perceptions of health consumers about current and feasible future services by pharmacists with a specific focus on CVD risk screening and management in Saudi Arabia. Methods: Semi-structured interviews were conducted with consumers with at least one modifiable CVD risk factor. The interviews were audio-recorded, transcribed verbatim, translated into English and then thematically analysed. Results: A total of 25 individuals, most of whom were Saudi (88%) and women (65%), participated in face to face interviews. Five main themes emerged from the analysis of consumers' responses. 1. Perception of pharmacists' role, the pharmacists' main role was perceived as medication supply. 2. Trust and satisfaction with current service, most participants appeared to have low trust in pharmacists. 3. Preferences for future pharmacy services, most participants were willing to engage in future pharmacy delivered CVD preventive health services, provided there was stringent regulation and oversight of the quality of such services. 4. Viability of new pharmacy services was raised with promotion of such services to the public, collaboration with other health professionals, financial incentivization and motivational rewards thought of as essential ingredient to ensure service feasibility. 5. Health beliefs and help seeking behaviours of consumers were diverse and low health literacy was evident; it was thought that pharmacists can help in these matters by educating and advocating for such consumers. Overall, the data suggested that clinical, communication and professional skills need to be enhanced among Saudi pharmacists to enable them to provide optimal patient cantered services. Conclusion: Health consumers participants were willing to participate and utilise CVD risk screening and management pharmacy-based services, when offered, provided their concerns are addressed. Therefore, in light of the burden of CVD disease in the country, development, implementation and evaluation of pharmacist provided CVD risk screening and management should be undertaken.